MODERN INFORMATION AND COMMUNICATION SYSTEMS TECHNOLOGIES IN CUSTOM SERVICE - Юдін, О.; Гулак, Н. (Science-based technologies, 2010)
The chart of structurally-logical of informatively-communication system and network of government custom service of Ukraine for the increase of efficiency of her functioning it was worked out on the base of method of the non-equilibrium position encoding of data for organization of the operative checking of custom posts system on the base of informative flows of data.